PREDIKSI KELULUSAN MAHASISWA MENGGUNAKAN ALGORITMA C4.5 (STUDI KASUS DI UNIVERSITAS PERADABAN) - Ade Fatma Ayu Rahman; Sorikhi .; sri wartulas (Indonesian Journal of Informatics and Research, 2020)
Students are an important parameter in implementing a study program, many students have different graduation rates, are on time and are not on time. This is an obstacle for the University in general because the number of graduations each year is one of the factors that will be assessed for applying for accreditation. This study aims to determine the level of accuracy of the C4.5 algorithm in predicting student graduation, using the C4.5 decision tree algorithm method. Student data used as attributes are IPK, credits, age, gender. The results of the analysis in this study indicate that the C4.5 algorithm can predict with an accuracy value of 88.07% with a precision of 91.79% and a recall of 95.34%.